Pharmacognostical and preliminary phytochemical studies of Urena lobata linn - Rinku Mathappan; V. Felix Joe; Prasanth V.V; Kamalakkanan Varirappan (International Journal of Phytomedicine, 2010)
In the present study was to determine the pharmacognostical and preliminary phytochemical analysis of Urena lobata Linn. In pharmacognostoical studies powder characteristics of leaf and stem, leaf constant and analytical parameters like ash values extractive value analysis of major elements and in preliminary phytochemical studies were carried out .All these characters were determined will help the researches in their phytochemical as well as pharmacognostical analysis of this species.